Modeling The Influence Of Slurry Temperature On Gold Leach And Adsorption Kinetics At The Fort Knox Mine, Fairbanks, Alaska - John T. Hollow; Eric M. Hill; Hsing K. Lin; Daniel E. Walsh (Society for Mining, Metallurgy & Exploration, 2005)
The Fort Knox Mine is located in Alaska’s interior where the average ambient air temperatures range from -24°C in January to 16°C in July. The mill processes a free milling gold ore utilizing both a gravity recovery circuit and conventional cyanide leach/carbon-in-pulp circuits. Plant slurry temperature cycles seasonally and allows for a unique opportunity to measure the impact temperature has on gold leach kinetics, carbon adsorption efficiency and cyanide destruction reactions. Mathematical models have been developed to accurately predict actual mill performance. This paper describes the development of the models and presents data that allow for a better understanding of the impact of circuit operating temperature on process efficiencies.